Correlation between Helicobacter Pylori Caga Antibody Serum and Gastric Premalignant Lesions in Helicobacter Pylori Patients - Monica, Clarisa; Sungkar, Taufik; Ilhamd (Journal of Society Medicine, 2023)
Introduction: Helicobacter pylori (H. pylori) is a spiral-shaped, anaerobic, and gram-negative pathogenic bacteria found in the gastric mucosa that causes chronic gastritis and gastric cancer. One of the most studied H. pylori virulence factors is the CagA protein in which positive anti-CagA antibodies increase the risk of malignancy in the stomach. This research was aimed to determine the correlations between Helicobacter pylori CagA antibody serum and gastric premalignant lesions in Helicobacter pylori patients. Method: This was a cross-sectional and analytic research. The sample of this study were patients diagnosed with Helicobacter pylori at Haji Adam Malik General Hospital in Medan who corresponded the inclusion criteria. The research was conducted from January to December 2022. The sampling technique used was consecutive sampling. Selected subjects underwent endoscopy and biopsy, as well as antibody detection of CagA, then the data analysis was carried out. Results: The number of samples that included in this study were 60 people. Based on demographic characteristics, the majority of patients were women, Batak ethnic, having a normal body mass index, not having a history of alcohol consumption, and non-smokers. The majority of people with Helicobacter pylori did not have CagA antibodies. There was a significant relationship (p=0.009) between  antibody of CagA and gastric premalignant lesions, as well as the prevalence ratio is 2.6. Conclusion: There is a correlation between antibody of CagA and gastric premalignant lesions in patients with Helicobacter pylori infection.